DEVELOPMENT AND VALIDATION ANALYSIS METHOD DETERMINATION OF RESIDUAL MEBENDAZOLE IN BOVINE MILK BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Ridho Wahyu Dianti, Aisyah
Background and purpose: Mebendazole (methyl-5-benzoyl-2-carbamate benzimidasole) is anthelmintic benzimidasole group used both for humans and livestock. Mebendazole commonly used in veterinary for the prevention and control of internal worm parasites in animals. The presence of veterinary drug residues in animal food products is regulated by the SNI 01-6366-2000. In this standard, maximum concentration of mebendazole residue in milk is 20 ng / mL. The purpose of this study was to develop a easy, fast and sensitive analytical methods which could detect mebendazole in food samples with low levels. Method: High Performance Liquid Chromatography assay was developed for mebendazol in milk samples. The mobile phase used was 0.05 M potassium dihydrogen phosphate pH 4.5-acetonitrile in the ratio 70:30, flow rate of 1.0 ml / min and UV detector at a wavelength of 246 nm using a column LiChrospher® 100 RP-C18 10 µm (4,6 x 250 mm). Milk extraction process was using liquidliquid extraction. Results: The method was validated by testing linearity, limit of detection, limit of quantitation, precision, and accuration. It have linear calibration curve obtained in the concentration range from 1,0 to 6,0 µg/mL with a linear regression equation was y = 106,99x + 34,107. The method showed a good linearity with a correlation coefficient of 0,9957. While the linear regression equation obtained using milk samples spiked was y = 111,72x + 5,639 with a correlation coefficient 0,9984. This method also has a limit of detection and quantitation limits were 0,53 µg/mL and 1,61 µg/mL. Percent coefficient of variance intraday precision are 1,09%; 2.34% and 1,99%, meanwhile the percent coefficient of variance interday precision are 0,46%. Recovery of mebendazol in milk samples are ranged from 89,49 to 108,76%. These results indicate the method which has been validated is used for the assay of determination mebendazole in the milk sample.